Stock assessment for the western winter-spring cohort of neon flying squid (Ommastrephes bartramii) using environmentally dependent surplus production models - Wang, Jintao; Yu, Wei; Chen, Xinjun; Chen, Yong (Scientia Marina, 2016)
The western winter-spring cohort of neon flying squid, Ommastrephes bartramii, is targeted by Chinese squidjigging fisheries in the northwest Pacific from August to November. Because this squid has a short lifespan and is an ecological opportunist, the dynamics of its stock is greatly influenced by the environmental conditions, which need to be considered in its assessment and management. In this study, an environmentally dependent surplus production (EDSP) model was developed to evaluate the stock dynamics of O. bartramii. Temporal variability of favourable spawning habitat with sea surface temperature (SST) of 21-25°C (Ps) was assumed to influence carrying capacity (K), while temporal variability in favourable feeding habitat areas with different SST ranges in different months (Pf) was assumed to influence intrinsic growth rate (r). The parameters K and r in the EDSP model were thus assumed to be linked to temporal variability in the proportion of Ps and Pf, respectively. According to Deviance Information Criterion values, the estimated EDSP model with Ps was considered to be better than the conventional surplus production model or other EDSP models. For this model, the maximum sustainable yield (MSY) varied from 210000 to 262500 t and biomass at MSY level varied from 360000 to 450000 t. The fishing mortality rates of O. bartramii from 2003 to 2013 were much lower than the fishing mortality at target level and MSY level (Ftar and FMSY) and stock biomass was higher than BMSY, suggesting that this squid was not in the status of overfishing and stock was not overfished. The management reference points in the EDSP model for O. bartramii were more conservative than those in the conventional model. This study suggests that the environmental conditions on the spawning grounds should be considered in squid stock assessment and management in the northwest Pacific Ocean.